Herpes and tinea in wrestling - Landry, G. L.; Chang, C. J.; Harmon, K. G.; Rubin, A. (The Physician and Sportsmedicine, 2004)
The two most troublesome skin infections in wrestlers are herpes gladiatorum and tinea gladiatorum. Determining whether athletes should or should not be disqualified from practice or competition because of these infections requires some expertise. Recommendations are presented to assist the practitioner in the care of these conditions in wrestlers and other athletes who have frequent skin-to-skin contact.